EKSPOSUR NILAI TUKAR DOLAR (US) PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - Mata, Vivilia Wulandari Tarru; Pangeran, Perminas (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT This research was intended to test the dollar (US) foreign exchange exposure towards the multinational company in Indonesia. This research used theory of hedging policy about the foreign exchange exposure. Foreign exchange exposure could be explained by the company’s internal variables, which are size, dividend payout ratio (DIV), quick ratio (QR), a market-to-book equity ratio (MBE) and long-term debt ratio (DE). The results showed that the dividend payout ratio and market-to-book equity ratio had an influence on the level of foreign exchange exposure. Keywords: foreign exchange exposure, hedging